Pengaruh Literasi Keuangan, Lifestyle Hedonis, dan Sikap Keuangan Pribadi terhadap Perilaku Keuangan Mahasiswa - Aghus Ali Awaluddin; Anna Widiastuti (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
This study aims to determine financial literacy, hedonic lifestyle, and personal financial attitudes towards financial behavior both partially and simultaneously in 2021 unisnu jepara management students. The population in this study were 2021 management students as many as 134 respondents. The research method used by researchers is quantitative method and the tests carried out are: validity test, reliability test, normality test, multicollinearity test, heterocedicity, multiple linear regression analysis, t test, f test, and coefficient of determination. The testing tool used is SPSS 30 software for windows. The results of this study indicate that partially financial literacy has a positive effect on financial behavior, partially hedonic lifestyle has a positive effect on financial behavior, partially personal financial attitudes have a positive effect on financial behavior, simultaneously financial literacy, hedonic lifestyle, and personal financial attitudes affect financial behavior in 2021 unisnu management students, then the percentage of contribution of the influence of independent variables including financial literacy, hedonic lifestyle, and personal financial attitudes on the dependent variable financial behavior is 0.602 or 60.2%